Plan de negocio para la producción y cría de novillos raza holstein en la finca Morrito, en el municipio de Belén Boyacá (2017)
In the following project a detailed review is made about the livestock sector more specifically in the guild of the production and breeding of calves with the purpose of double purpose, all with the need to respond to the investor of the El Morrito farm if the project that is has been developing is viable, reviewing each of the parts of the development of this, confirming financially how real is the profit and if it is the one expected by the investor, with the aim of detailing what costs are incurred and how to give it better exploitation analyzing the meat market.